A novel role of suppressor of cytokine signaling‐2 in the regulation of TrkA neurotrophin receptor biology. (4th March 2014) - Uren, Rachel T.; Turbić, Alisa; Wong, Agnes W.; Klein, Reuben; Murray, Simon S.; Turnley, Ann M.
Abstract Suppressor of cytokine signaling‐2 (SOCS2) is a regulator of intracellular responses to growth factors and cytokines. Cultured dorsal root ganglia neurons from neonatal mice with increased or decreased SOCS2 expression were examined for altered responsiveness to nerve growth factor (NGF). In the presence of NGF, SOCS2 over‐expression increased neurite length and complexity, whereas loss of SOCS2 reduced neurite outgrowth. Neither loss nor gain of SOCS2 expression altered the relative survival of these cells, suggesting that SOCS2 can discriminate between the differentiation and survival responses to NGF. Interaction studies in 293T cells revealed that SOCS2 immunoprecipitates with TrkA and a juxtamembrane motif of TrkA was required for this interaction. SOCS2 also immunoprecipitated with endogenous TrkA in PC12 Tet‐On cells. Over‐expression of SOCS2 in PC12 Tet‐On cells increased total and surface TrkA expression. In contrast, dorsal root ganglion neurons which over‐expressed SOCS2 did not exhibit significant changes in total levels but an increase in surface TrkA was noted. SOCS2‐induced neurite outgrowth in PC12 Tet‐On cells correlated with increased and prolonged activation of pAKT and pErk1/2 and required an intact SOCS2 SH2 domain and SOCS box domain. This study highlights a novel role for SOCS2 in the regulation of TrkA signaling and biology. <boxed-text content-type="graphic" id="jnc12671-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Neurotrophins such as Nerve growth factor (NGF) are important for the neurite outgrowth and survival of sensory neurons. Increased expression of SOCS2 enhanced NGF‐dependent neurite outgrowth and increased TrkA receptor surface localization in dorsal root ganglion neurons and PC12 cells. This correlated with increased and prolonged activation of pAKT and pErk1/2. In 293T cells SOCS2 was shown to interact with the TrkA receptor in the juxtamembrane region. We thus propose that SOCS2 is a novel regulator of neurotrophin signaling.